2019
DOI: 10.3390/nu11122944
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk’s Hidden Gift: Implications of the Milk Microbiome for Preterm Infants’ Health

Abstract: Breastfeeding is considered the gold standard for infants’ nutrition, as mother’s own milk (MOM) provides nutritional and bioactive factors functional to optimal development. Early life microbiome is one of the main contributors to short and long-term infant health status, with the gut microbiota (GM) being the most studied ecosystem. Some human milk (HM) bioactive factors, such as HM prebiotic carbohydrates that select for beneficial bacteria, and the specific human milk microbiota (HMM) are emerging as early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 83 publications
0
39
0
3
Order By: Relevance
“…Choosing tertiary hospitals in major urban centres allowed a representative sampling of mothers who frequent them for obstetrical purposes [33]. Focusing solely on young, healthy peripartum mothers belonging to the same geo-ethnic mix increases the likelihood of obtaining beneficial commensals that are effective for that population [7, 24]. All of the LAB genera from human milk found in this study have been reported as pioneering colonizers of a healthy, breastfed infant gut [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Choosing tertiary hospitals in major urban centres allowed a representative sampling of mothers who frequent them for obstetrical purposes [33]. Focusing solely on young, healthy peripartum mothers belonging to the same geo-ethnic mix increases the likelihood of obtaining beneficial commensals that are effective for that population [7, 24]. All of the LAB genera from human milk found in this study have been reported as pioneering colonizers of a healthy, breastfed infant gut [34].…”
Section: Discussionmentioning
confidence: 99%
“…The human colonic epithelial cell line, T84, was obtained from the Department of Medicine, UCSD, and cultured as described previously [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of bacteria in human milk is not well-established. Two different routes, which are probably not mutually exclusive, have been proposed: (i) surface skin contamination and retrograde flow during breastfeeding and (ii) translocation through a more speculative gut-mammary route ( 153 ). The assumption that microbes in breast milk contribute to the establishment of the infant intestinal microbiome is supported by several studies in mother-infant pairs using sequencing techniques and demonstrating that breast milk and term infants' feces share specific microbial strains of Bifidobacterium, Lactobacillus, Enterococcus , and Staphylococcus ( 65 69 ).…”
Section: Maternal Factorsmentioning
confidence: 99%
“…A recent review confirmed the importance of breastfeeding in protecting against many infections; compared to infants given formula, there are significantly lower rates of diarrhoeal disease and lower respiratory tract infection, with a reduction of 50% or more to be expected, especially in infants under six months of age [ 11 , 12 ]. Exclusive breastfeeding is important for establishing a healthy microbiome, which has an important protective effect against chronic disease later in life, including obesity [ 13 , 14 , 15 ]. Children who had been breastfed for at least six months were less likely to be overweight or obese later [ 16 ].…”
Section: Introductionmentioning
confidence: 99%